2018
DOI: 10.1111/jam.14111
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic fungal endophytePhomopsis liquidambari-rice system promotes nitrogen transformation by influencing below-ground straw decomposition in paddy soil

Abstract: Aims: To explore if and how symbiotic Phomopsis liquidambari-rice system influences below-ground straw decomposition and then nitrogen(N) transformation in response to environmental N levels. Methods and Results: Litter bag experiments were utilized to trace the decay process during rice growth phases (seedling (T1), tillering (T2), heading (T3) and maturing (T4) stage), with (E+) and without endophyte (EÀ), under low (LN), medium (MN) and high nitrogen (HN) supply. Litter, soil and plant samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Besides the low concentration of nitrogen in the soil, rice straw is also characterized by low levels of N, around 0.95% (Sun et al 2019). Moreover, the sample collection period was less than 12 days after the knife-roller pass, a period which was not enough to release nitrogen from the plant residues.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the low concentration of nitrogen in the soil, rice straw is also characterized by low levels of N, around 0.95% (Sun et al 2019). Moreover, the sample collection period was less than 12 days after the knife-roller pass, a period which was not enough to release nitrogen from the plant residues.…”
Section: Resultsmentioning
confidence: 99%
“…This result is contrary to that of Blum et al, who demonstrated that carbon sources, such as glucose, may reduce microbial metabolism of the allelochemical ρ ‐coumaric acid. A recent study demonstrated that P. liquidambari can perform a lifestyle transition from endophytism to saprophytism and promote the destructive decay of litterfall . Thus, for endophytic microorganisms, the ability to utilize recalcitrant compounds (such as phenolic allelochemicals) as carbon sources might be necessary to survive long periods outside the host habitat without the labile energy.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that the broad‐spectrum endophyte, Phomopsis liquidambari B3, which was isolated from the inner bark of the Bischofia polycarpa stem, can establish a mutualistic relationship with peanut roots and promote peanut nodulation and growth . Moreover, this fungus has been shown to migrate from plant roots to the rhizosphere and then survive in soil for a long time . P. liquidambari has also been proven to decompose 4‐hydroxybenzoic acid, ferulic acid, and luteolin effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…liquidambaris is able to degrade soil recalcitrant organic matter and survive in harsh environments [26][27][28][29][30]. Because of the strong saprophytic ability, Ph.…”
Section: Introductionmentioning
confidence: 99%